PENGARUH MODEL PEMBELAJARAN STAD BERBANTUAN MEDIA SNAKES LADDERS GAME TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD NEGERI 42 PALEMBANG - Tri Hidayati, Vina; Rizhardi, Rury; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model assisted by Snakes and Ladders Game media on student learning outcomes in mathematics subjects on the circumference of flat shapes for grade III students. The research method used is quantitative with a quasi-experimental design. The subjects in this study consisted of two classes, namely the experimental class using the STAD model assisted by snakes and ladders media, and the control class using conventional learning. Data collection techniques in this study were tests and documentation. The test has been validated and declared valid, and a reliability test was carried out and declared reliable, with a medium category difficulty index and good category discrimination power. Before conducting the hypothesis test, a prerequisite test was carried out, namely a normality test and a homogeneity test, and the results showed that the data were normally distributed and homogeneous. The data analysis technique used a hypothesis test with t-test analysis. The instrument used in data collection was a learning outcome test in the form of pretest and posttest questions. The results of data analysis using the t-test showed a significant difference between the learning outcomes of students in the experimental class and the control class, with a significance value (2-tailed) of 0.004 <0.05. The mean difference value of -11.724 indicates that the average learning outcomes of students in the experimental class are higher than those in the control class. It can be concluded that the application of the STAD learning model assisted by the Snakes and Ladders Game media has a significant effect on improving students' mathematics learning outcomes